Soil conditions and land use intensification effects on soil microbial communities across a range of European field sites. (September 2015) - Thomson, Bruce C.; Tisserant, Emilie; Plassart, Pierre; Uroz, Stéphane; Griffiths, Rob I.; Hannula, S. Emilia; Buée, Marc; Mougel, Christophe; Ranjard, Lionel; Van Veen, Johannes A.; Martin, Francis; Bailey, Mark J.; et al.
Abstract: Intensive land use practices necessary for providing food and raw materials are known to have a deleterious effect on soil. However, the effects that such practices have on soil microbes are less well understood. To investigate the effects of land use intensification on soil microbial communities we used a combined T-RFLP and pyrosequencing approach to study bacteria, archaea and fungi in spring and autumn at five long term observatories (LTOs) in Europe; each with a particular land use type and contrasting levels of intensification (low and high). Generally, due to large gradients in soil variables, both molecular methods revealed that soil microbial communities were structured according to differences in soil conditions between the LTOs, more so than land use intensity. Moreover, variance partitioning analysis also showed that soil properties better explained the differences in microbial communities than land use intensity effects. Predictable responses in dominant bacterial, archaeal and fungal taxa to edaphic conditions (e.g. soil pH and resource availability) were apparent between the LTOs. Some effects of land use intensification at individual field sites were observed. However, these effects were manifest when land use change affected soil conditions. Uniquely, this study details the responses of different microbial groups to soil type and land use intensification, and their relative importance across a range of European field sites. These findings reinforce our understanding of drivers impacting soil microbial community structure at both field and larger geographic scales. Highlights: Manuscript provides information on soil biodiversity in Europe. Five long term field sites, with different soil types and land uses, were sampled. Genetic structure and diversity of microbial communities were assessed. Microbial communities were strongly impacted by land use and edaphic parameters. Bacteria, archaea and fungi were differentially impacted by the intensification.